Transforming Digital Experience into Literacy Practice through Phenomenological Consciousness among Gen Alpha Children - Helmanto, Fachri; Efendi, Irwan; Ichsan, Muhammad (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study explores how digital experiences are transformed into meaningful literacy practices in children of Generation Alpha through the lens of phenomenological consciousness. Anchored in Husserl’s framework of noema and noesis, this research examines how children perceive and internalize digital content, and how these experiences shape their narrative imagination and literacy production. Using a qualitative narrative inquiry, the study involved primary school students from four regions in Indonesia, collecting data through interviews, document analysis, and storytelling outputs. The findings reveal three noetic pathways: (1) digital perception as lived experience, (2) imaginative reconstruction through internalized digital stimuli, and (3) narrative actualization in multimodal literacy forms. This study proposes a synthetic model for integrating digital perception into pedagogical strategies that enhance critical and creative literacy. The implications suggest the need to reposition digital media not merely as learning tools, but as catalysts for cognitive-intentional transformation in young learners. The phenomenological perspective offers a novel orientation in literacy pedagogy amid the rise of digital-native generations.